Evaluation and development of antibacterial fabrics using Pongamia pinnata extracts. (9th September 2019) - Andra, Swetha; Muthalagu, Murugesan; Jeevanandam, Jaison; Sekar, Durga Devi; Ramamoorthy, Rajalakshmi
Abstract : Purpose: A widespread focus on the plant-based antimicrobial cotton fabric finishes has been accomplished with notable importance in recent times. The antimicrobials prevent microbial dwelling in fabrics, which causes severe infections to the fabric users. Chemical disinfectants were conventionally used in fabrics to address this challenge; however, they were found to be toxic to humans. Thus, the present study aims to deal with the utilization of phytochemical extracts from different parts of Pongamia pinnata as antimicrobial coatings in cotton fabrics. Design/methodology/approach: The root, bark and stem were collected and washed several times using tap water. Then, the leaves were dried at room temperature and the root and bark were dried using an oven at 40ºC. After drying, they were ground into fine powder and extracted with ethanol using the Soxhlet apparatus. After that the extract was coated on the fabric tested for antimicrobial studies. Findings: The results reported that the leaf extract of P. pinnata -coated fabric exhibited enhanced antibacterial property towards gram-negative Escherichia coli bacteria, followed by root, bark and stem. The wash durability test in the extract-coated fabric samples revealed that dip-coating retained antibacterial activity until five washes. Thus, the current study clearly suggests that the leaf extract from P. pinnata is highly useful to develop antibacterial cotton fabrics as health-care textiles. Originality/value: The novelty of the present work is to obtain the crude extract from the leaves, bark, root and stem of P. pinnata and evaluate their antibacterial activity against E. coli, upon being coated on cotton fibres. In addition, the extracts were subjected to wash durability analysis to study the coating efficiency of the phytochemicals in cotton fabrics and a probable mechanism for the antibacterial activity of P. pinnata extracts was also presented.